Flash Flood Assessment Using GIS and the Frequency Ratio Bivariate Statistical Model – Case Study, Codlea, Romania. - Diana Marinela VASILE; Mihnea Cristian POPA; Florentina TOMA; Daniel Constantin DIACONU (Aerul şi Apa: Componente ale Mediului, 2021)
Floods are one of the biggest natural disasters, causing significant economic and human losses. Regardless of the degree of development of urban or rural systems, floods account for about a third of all-natural disasters globally. Identifying areas vulnerable to floods is essential for better management and mitigation of their effects. The research aims to identify areas vulnerable to floods in the city of Codlea, Brașov County. Annually, the city records significant floods, one of the determining factors being its location, near the southern slope of the Perșani Mountains. The research proposes the Flash Flood Potential Index (FFPI) computation by combining GIS techniques with the Frequency Ration bivariate statistical model. The correlation of various flash-flood conditioning variables allowed us to compute the FFPI. The methodological approach could represent an essential tool for local authorities for better flood risk management.